Impacts of government debt on output growth, private consumption and productivity in ASEAN-4 countries - Hajian, Hoda (2019)
The macroeconomic effects of government debt are a long debated and recurring economic issue. Recently, as world government debt has reached unprecedented levels, the issue has been of particular focus among economists and policy makers. Although mainstream economics holds a negative view on the effects of high and increasing government debt, and the existing empirical panel studies tend to agree with that conclusion, the effect of moderate debt levels on emerging economies is rather ambiguous. Moreover, recent studies emphasize that the effect of government debt is country specific, yet extant empirical evidence is almost always based on large panel samples. This study attempts to empirically investigate the relationship between government debt and macroeconomic factors in four emerging ASEAN countries over the past three decades (1985-2014), namely Indonesia, Malaysia, the Philippines and Thailand (ASEAN-4). The first objective is to investigate the relationship between government debt and output growth. In order to do that, a reduced form model of endogenous growth using a VAR framework is employed. Utilising Generalized Impulse-Response (GIR) analysis, this study traced the responses of output growth index, growth factors such as private investment and human capital stock, and government debt itself to a shock to government debt. Conforming to causality result, the response of economic growth in Indonesia and Malaysia were insignificant, whereas in the Philippines and Thailand some evidence of positive and significant impact was found. For the second objective, the effect of government debt on private consumption in the long-run is analysed. Given the mostly insignificant results of the first objective, the question may arise of whether this is due to Ricardian implications, which state that debt does not have any effect on economic growth. The consumption model in the second objective tests Ricardian versus neoclassical hypotheses of consumer behaviour. The results strongly reject Ricardian (or tax-discounting) behaviour, and are in line with neoclassical theory. Finally, as the third objective the long term effect of government debt on total factor productivity (TFP) growth is investigated. On one hand, TFP is an increasingly important growth factor for ASEAN-4 economies. On the other hand, studies show that debt could affect TFP growth, which could have an impact on the ASEAN-4 countries. The results show that government debt has a positive effect on TFP growth, which is statistically significant in Indonesia and Malaysia but insignificant in Thailand. However, debt adversely affects TFP growth in the Philippines. In summary, the result of all three objectives are compatible with endogenous neoclassical growth models, which consider the positive economic effects of government debt if it is spent efficiently on productive projects. The policy implications based on the findings can be summarized as follows: in Indonesia and Malaysia, stronger positive results are plausible if improvement in current fiscal policy is continued within the same range of government debt. In the Philippines, given the economic conditions, the desirable policy is one which helps to reduce government debt. In Thailand, government debt can stimulate economic growth in the medium term while the government is able to reduce its debt at the same time.